Analysis of The Influence of Auditor Competency, Auditor Independence, Audit Experience and Auditor Ethics on Audit Quality (Case Study at a Public Accounting Firm in Semarang) - Wahyuningsih, Panca (Library of Sultan Agung Islamic University, 2024)
This research aims to test and analyze whether auditor competence, auditor independence, auditor experience, and auditor ethics affect on audit quality. The population in this study were auditors who worked in Public Accounting Firm in Semarang. Sampling was carried out using the cencus method and the number of samples was 73 respondents. The type of data used is primary data. This study uses a questionnaire to collect data. The test techniques used are validity test, reliability test, classic assumption test including normality test, multicolinearity test, and heteroscedasticity test. Hypothesis testing in this study used multiple linear tests with SPSS version 26. The result of this study indicate that Auditor Competence has a negative and insignificant efffect on Audit Quality. Auditor experience has a positive and significant effect on audit quality. Auditor ethics has a positive and significant effect on Audit Quality.